Die Zukunft der Industrie: technologiefundierte Dienstleistungen - Birger P. Priddat (Wirtschaftsdienst, 2012)
Häufig ist zu hören, dass die Industrie ein aussterbender Wirtschaftszweig sei. Die Zukunft gehöre den Dienstleistungen und der Wissensproduktion. Tatsächlich basiert die moderne Ökonomie ganz wesentlich auf Informationstechnologie. Diese bedarf aber der Hardware. Dienstleistungen und Industrie sind eine enge Beziehung eingegangen, die kaum mehr zu trennen ist. Dabei ist ein Teil dieses Konglomerats von der ökonomischen in die Privatsphäre übergegangen. – – The industrial society has become history, substituted by the service economy, the knowledge economy or the information economy. But industry has only changed its form: the IT processes in particular are fundamentally industry-based, not only because of the hardware required by the informational processes, but also due to their infi ltration into all service economy dimensions and our everyday lives. Modern life does not work without the IT infrastructure. Man-machine interfaces have become micro-industry structures, which transform IT-users into producers. Besides, all ecological problems and climate change challenge our industrial competences. Industry is the tacit power of our time.
Keywords: L16; O31; O33; 330; Technischer Fortschritt; Industrieller Strukturwandel; Industrielle Produktion; Welt